Skin Responses in Newly Diagnosed Polyneuropathy, Organomegaly, Endocrinopathy, Monoclonal Gammopathy, and Skin Changes (POEMS) Syndrome After Therapy With Low-Dose Lenalidomide Plus Dexamethasone - Gao, Yajuan; Zhang, Shiyu; Yang, Lu; Li, Jian; Liu, Yuehua; Wang, Tao (Frontiers in Immunology, 2021)
Background: Polyneuropathy, organomegaly, endocrinopathy, monoclonal gammopathy, and skin changes (POEMS) syndrome is a rare paraneoplastic disease with a high prevalence of skin symptoms. Few studies have focused on skin responses to systemic treatment of this disease. Objective: To evaluate skin responses after treatment with low-dose lenalidomide plus dexamethasone and determine their relationship with vascular endothelial growth factor (VEGF) and hematological responses. Methods: A total of 41 consecutive Chinese patients who were at least 18 years of age with newly diagnosed POEMS syndrome were enrolled. 36 of them completed 12 cycles of treatment. Skin, serum VEGF, hematological and neurological responses were documented at 1, 2, 3, 6, 9 and 12 months during treatment. Results: Skin manifestations were not associated with serum VEGF levels at baseline. Of the patients with hyperpigmentation, hemangiomas, hypertrichosis, white nails, or acrocyanosis separately, 26/34 (76.5%), 11/30 (36.7%), 14/15 (93.3%), 21/21 (100%), and 4/4 (100%) achieved complete responses at 12 months. Reduction in hyperpigmentation after 12 months reflected a good VEGF response (P=0.017). Conclusion: Low-dose lenalidomide plus dexamethasone therapy is effective in reversing skin changes in patients with POEMS syndrome. Clinicaltrials.gov listing: NCT01816620. Keywords: POEMS syndrome; skin changes; lenalidomide; dexamethasone; prospective studies